Use of the Walking Impairment Questionnaire and Walking Estimated-Limitation Calculated by History questionnaire to detect maximal walking distance equal to or lower than 250 m in patients with lower extremity arterial disease - Tollenaere, Quentin; Métairie, Antoine; Le Pabic, Estelle; Le Faucheur, Alexis; Mahé, Guillaume (Frontiers in Cardiovascular Medicine, 2023)
Objective The objective was to assess the accuracy and optimal threshold of the Walking Impairment Questionnaire (WIQ) and the Walking Estimated-Limitation Calculated by History (WELCH) questionnaire in identifying patients with a maximal walking distance (MWD) below or equal to 250 m. Methods This retrospective study screened 388 consecutive patients with suspected symptomatic lower extremity arterial disease (LEAD). Collected data included the patient's history, resting ankle-brachial index, WIQ, and WELCH. MWD was assessed with a treadmill test at 2 mph (3.2 km/h) with a 10% grade. An optimized threshold for detection of MWD ≤ 250 m was determined for each questionnaire via receiver operating characteristic (ROC) curves. Subsequently, multivariate analysis was performed to build a new simple score to detect MWD ≤ 250 m. Results The study included 297 patients (63 ± 10 years old). With a threshold of ≤ 64%, the WIQ predicted MWD ≤ 250 m with an accuracy of 71.4% (66.2, 76.5%). With a threshold of ≤ 22, the WELCH predicted a treadmill walking distance of ≤ 250 m with an accuracy of 68.7% (63.4, 74.0%). A new score with only four “yes or no” questions had an accuracy of 71.4% (66.3, 76.6%). Items on this new score consisted of the level of difficulty of walking 1 block, declared maximum walking distance, usual walking speed, and maximum duration of slow walking. Conclusion A WIQ score ≤ 64% and a WELCH score ≤ 22 help to predict a walking distance of ≤ 250 m in a treadmill test at 2 mph (3.2 km/h) with a 10% grade. A 4-item score could be used for rapid evaluation of walking distance among patients with LEAD, but the validity of this 4-item score requires further confirmation studies.